Human aspects of IT for the aged population : third International Conference, ITAP 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings /: third International Conference, ITAP 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings. (2017) - Unknown
No abstract available